Parallel Warburg Elements Describe Ionic Transport in Nanopores - Filipe Henrique; Ankur Gupta (PRX Energy)
For several decades, ionic transport within a charged nanopore has been represented by a resistor-capacitor transmission line circuit, where charging electrical double layers are modeled as capacitors, and the resistance to ionic current is modeled as resistors. However, these circuits fail to account for oscillations observed in experimental Nyquist plots of impedance, which are attributed ad hoc to effects such as complex porous structures or chemical reactions. Here we show that diffusivity asymmetry between ions in confinement—overlooked in previous studies—produces Nyquist plots with two turns. Additionally, we demonstrate that ionic transport in a nanopore is more accurately described by two resistor-capacitor circuits. The results show that an impedance response of ionic transport in nanopores for arbitrary Debye lengths is better captured by two Warburg elements in parallel than a single Warburg element. Our findings provide a framework for describing ionic transport in nanopores, with implications for electrochemical technologies using nanoporous electrodes such as supercapacitors, capacitive desalination, and fuel cells.